2020
DOI: 10.1186/s13075-020-02321-w
|View full text |Cite
|
Sign up to set email alerts
|

The plasma level of mCRP is linked to cardiovascular disease in antineutrophil cytoplasmic antibody-associated vasculitis

Abstract: Background C-reactive protein (CRP) has two natural isomers: C-reactive protein pentamer (pCRP) and C-reactive protein monomer (mCRP). The levels of CRP are significantly elevated in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). mCRP not only activates the endothelial cells, platelets, leukocytes, and complements, but also has a proinflammatory structural subtype that can localize and deposit in inflammatory tissues. Thus, it regulates a variety of clini… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
1
9
1
Order By: Relevance
“…The ratio of mCRP/pCRP also differed, showing higher ratios in SLE compared to AAV. In contrast to Wu et al [ 30 ], mCRP in our study did not correlate with BVAS in AAV patients (rho = 0.17, p = 0.37). However, in general, the patients with AAV included herein overall had less severe disease, which could indicate that the levels of mCRP is greater at even higher degree of disease activity than the patients in this study had.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The ratio of mCRP/pCRP also differed, showing higher ratios in SLE compared to AAV. In contrast to Wu et al [ 30 ], mCRP in our study did not correlate with BVAS in AAV patients (rho = 0.17, p = 0.37). However, in general, the patients with AAV included herein overall had less severe disease, which could indicate that the levels of mCRP is greater at even higher degree of disease activity than the patients in this study had.…”
Section: Discussioncontrasting
confidence: 99%
“…However, in general, the patients with AAV included herein overall had less severe disease, which could indicate that the levels of mCRP is greater at even higher degree of disease activity than the patients in this study had. Comparisons between this study and the study by Wu et al [ 30 ] shows that the level of mCRP in AAV differs greatly, where the patients herein had considerably lower levels. However, the mCRP levels in our study are more approximate to those reported by Chen et al [ 57 ], and in line with other autoimmune disorders and with patients of high CRP [ 58 60 ].…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…More recently, Wu et al . [ 18 ] demonstrated that a C-reactive protein monomer (mCRP), which is responsible for activating platelets, complement and pro-inflammatory cytokines, was associated with CVD in AAV patients. This strengthens the link between AAV and CVD independent of conventional risk factors.…”
Section: Disease Activity Endothelial Dysfunction and Accelerated Ath...mentioning
confidence: 99%